Advancing rare disease policy in Latin America: a call to action - Daniel Wainstock; Amiel Katz (Elsevier, 2023)
Summary: People living with a rare disease are amongst the most vulnerable groups in society. They have been historically marginalised and systematically stigmatised. It is estimated that 300 million people worldwide live with a rare disease. Despite that, many countries today, especially in Latin America, still lack consideration of rare diseases in public policies and national laws. Based on interviews with patient advocacy groups in Latin America, we aim to provide recommendations for lawmakers and policymakers in Brazil, Peru, and Colombia on how to improve public policies and national legislation for persons living with rare diseases in these three countries.